Single and combined IL28B, ITPA and SLC28A3 host genetic markers modulating response to anti-hepatitis C therapy. (December 2011) - Lötsch, Jörn; Hofmann, Wolf Peter; Schlecker, Christina; Zeuzem, Stefan; Geisslinger, Gerd; Ultsch, Alfred; Doehring, Alexandra
Advances in hepatitis C pharmacogenomics identified modulations of a sustained virologic response (SVR) by frequent IL28B gene variants and of ribavirin-induced hemolysis by frequent ITPA gene variants. These associations have been widely reproduced in various ethnicities, clinical settings and hepatitis C viral genotypes. The IL28B minor alleles rs8099917G, rs12979860T and rs12980275G have been associated with non-SVR whereas the ITPA minor alleles rs1127354A and rs7270101C were associated with less hemolytic side effects, an effect also attributed to a nucleoside transporter gene SLC28A3 rs10868138G/rs56350726T haplotype. The significance levels of these associations, especially in genome-wide studies, were very high. We nevertheless tested how good clinical outcomes of peginterferon α/ribavirin therapy, such as SVR or hemolytic side effects, were predicted by these variants. An analysis in an example dataset of 115 patients revealed that the prediction of non-SVR or hemolysis by single variants was often only slightly better than guessing. Using combinations of IL28B variants provided a higher accuracy (64.5%) of predicting non-SVR than with single IL28B variants (accuracy 60–63%). Similarly, a decline in blood hemoglobin by ≥3 g/dl could be better predicted at an accuracy of 70% (10% better than guessing) with a combination of an ITPA variant with a nucleoside transporter gene ( SLC28A3 ) haplotype. Thus, genotyping information about single IL28B or ITPA variants is reproducibly and statistically significantly associated with hepatitis C therapy outcomes; however, the clinical predictive utility of single variants can be increased by combinations of genotypes.